Highly Sensitive Textile-Based Capacitive Pressure Sensors Using PVDF-HFP/Ionic Liquid Composite Films - Keum, Kyobin (Sensors (Basel), 2021)
Textile-based pressure sensors have garnered considerable interest in electronic textiles due to their diverse applications, including human–machine interface and healthcare monitoring systems. We studied a textile-based capacitive pressure sensor array using a poly(vinylidene fluoride)-co-hexafluoropropylene (PVDF-HFP)/ionic liquid (IL) composite film. By constructing a capacitor structure with Ag-plated conductive fiber electrodes that are embedded in fabrics, a capacitive pressure sensor showing high sensitivity, good operation stability, and a wide sensing range could be created. By optimizing the PVDF-HFP:IL ratio (6.5:3.5), the fabricated textile pressure sensors showed sensitivity of 9.51 kPa(−1) and 0.69 kPa(−1) in the pressure ranges of 0–20 kPa and 20–100 kPa, respectively. The pressure-dependent capacitance variation in our device was explained based on the change in the contact-area formed between the multi-filament fiber electrodes and the PVDF-HFP/IL film. To demonstrate the applicability and scalability of the sensor device, a 3 × 3 pressure sensor array was fabricated. Due to its matrix-type array structure and capacitive sensing mechanism, multi-point detection was possible, and the different positions and the weights of the objects could be identified.